2005
DOI: 10.21273/hortsci.40.4.1057c
|View full text |Cite
|
Sign up to set email alerts
|

(214) Brassinosteroid-induced Femaleness in Cucumber and Relationship to Ethylene Production

Abstract: The cucurbit family is noted for diversity in sex expression phenotypes. Typically, a phase of male flowers precedes the appearance of female or hermaphrodite flowers. Sex determination of individual flowers is regulated by genetic, environmental, and hormonal factors. Ethylene, auxins, and gibberellins all influence flower sex, with ethylene, which promotes femaleness, playing a predominant role. In this study, we tested whether brassinosteroids, a more recently identified class of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The role of BR in sex determination of cucurbit species is not clear, but it is well known that it induces the production of ethylene in several plant species (Arteca and Arteca, 2008), including cucurbits (Guo et al, 2010). Thus, it is suggested that the effect of brassinosteroids on sex expression in cucumber is also mediated by ethylene (Papadopoulou and Grumet, 2005). In Cucumis pepo, BR may regulate the induction of carpellate development, although this regulation is genotype dependent (Golenberg and West, 2013).…”
Section: Sex Differential Gene Selectionmentioning
confidence: 99%
“…The role of BR in sex determination of cucurbit species is not clear, but it is well known that it induces the production of ethylene in several plant species (Arteca and Arteca, 2008), including cucurbits (Guo et al, 2010). Thus, it is suggested that the effect of brassinosteroids on sex expression in cucumber is also mediated by ethylene (Papadopoulou and Grumet, 2005). In Cucumis pepo, BR may regulate the induction of carpellate development, although this regulation is genotype dependent (Golenberg and West, 2013).…”
Section: Sex Differential Gene Selectionmentioning
confidence: 99%
“…The application of brassinosteroids in cucumber causes earlier and increased female flower production, and the effects may be mediated, at least in part, by the brassinosteroid-induced production of ethylene (Papadopoulou and Grumet, 2005). TLP is a potential substrate of brassinosteroidinsensitive 1, which can regulate certain biochemical activities near the plasma membrane to control plant growth (Nam and Li, 2004).…”
Section: Involvement Of Differentially Expressed Genes In Sex Determimentioning
confidence: 99%
“…BR mutations in Arabidopsis are associated with abnormal vascular development with increased phloem differentiation relative to xylem (Cano-Delgado et al 2004). We also have observed effects of BR treatment leading to distorted vascular development in cucumber (Papadopoulou and Grumet 2005). However, vascular bundles in PI308916 appeared normal; the disorganized cellular arrangement in PI308916 was associated with the interfascicular cortex region.…”
Section: Genetic Basis For the Compact Traitmentioning
confidence: 66%